Quaternary glaciations : extent and chronology. - Ehlers, Jurgen, 1948-; Gibbard, Philip L. (Philip Leonard), 1949- (Developments in Quaternary science, 2004)
This book is the second of three volumes in which the recent knowledge of the extent and chronology of Quaternary glaciations has been compiled on a global scale. This information is seen as a fundamental requirement, not only for the glacial community, but for the wider user-community of general Quaternary workers. In particular the need for accurate ice-front positions is a basic requirement for the rapidly growing field of palaeoclimate modelling. In order to provide the information for the widest-possible range of users in the most accessible form, a series of digital maps was prepared. The glacial limits were mapped in ArcView, the Geographical Information System (GIS) used by the work group. Included with the publication is a CD with digital maps, showing glacial limits, end moraines, ice-dammed lakes, glacier-induced drainage diversions and the locations of key sections through which the glacial limits are defined and dated. The last deglaciation is also shown in 500 year time-steps. The digital maps in this volume cover the USA and Canada and include Greenland and Hawaii. Both overview maps and more detailed maps at a scale 1: 1,000,000 are provided. Also available: Part I: Europe, ISBN 0-444-51462-7 Part III: South America, Asia, Africa, Australia, Antarctica, ISBN 0-444-51593-3.